(untitled) (In situ, 2025)
The shipwreck near Cape Ratac on the island of Koločep is an exceptionally valuable underwater archaeological site dating from the Early Modern Period. Despite its significance, the site has not been adequately preserved, and its condition continues to deteriorate due to unauthorized diving activities. During an expert inspection and surface cleaning carried out in 2024, numerous items from the ship’s equipment and cargo were recovered. Additionally, the remains of the ship’s wooden structure were found to be in excellent condition. Although the site is currently protected by geotextile, this is only a temporary measure. Therefore, continued archaeological research appears to be the most effective strategy for ensuring the site’s long-term protection.